IMPLEMENTASI E-GOVERNMENT PADA DINAS PARIWISATA PROVINSI BALI MELALUI PLATFORM DIGITAL SEBAGAI UPAYA PEMULIHAN PARIWISATA - Ganiswari, Ni Kadek Nia; Yudartha, I Putu Dharmanu; Wijaya, Komang Adi Sastra (CITIZEN CHARTER; Vol 4 No 1 (2024): Vol.4 No.1, 2024)
The tourism sector is one of the potential job for the community, especially for people of Indonesia. The spread of the COVID-19 chain has created a deterioration in the economy of Bali Province. In this case, Bali Tourism Office has the authority to take care of the government affairs of Bali Province especially tourism. One of the efforts made is to do virtual promotions using social media and websites. This research looks at the implementation of e-government through digital platforms as an effort to recover tourism. The data collection process uses qualitative research methods. Data were obtained by conducting direct observation activities, interviews, and literature studies. The results showed that the implementation of e-government on the digital platform owned by Bali Tourism Office has been carried out effectively, but there is still a need for optimization and improvement efforts in several aspects. Keywords: Implementation, E-Government, Digital Platform and Tourism